A Plasmonic Photonic Crystal Fiber Sensor with Simplified Features for Identifying Unidentified Analytes - Yasser, Hassan; Benhaliliba, Mostefa (University of Thi-Qar Journal of Science, 2024)
In this paper, we present a novel method for building a plasmonic photonic crystal fiber (PCF) sensor with simplified features to identify unknown analytes. Using the special parameters of plasmonic PCFs, the suggested sensor increases the sensitivity and specificity of target analyte detection. We provide a streamlined design approach that reduces manufacturing complexity without sacrificing reliable performance, opening up the sensor to new useful applications. We show the optimal structure parameters for optimizing sensitivity using the finite element method in the COMSOL environment. The suggested configuration attained strong spectral sensitivity throughout an extensive range of the analyte's refractive indices.  Furthermore, a perfect linear connection was established between the analyte's refractive index and the resonant wavelength, qualifying the sensor for usage across the whole range of the analyte's refractive indices.